2017
DOI: 10.1002/phar.1942
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide-Associated Neutropenia

Abstract: Drug-induced neutropenia and agranulocytosis are rare adverse events but can be fatal. Neutropenia can be induced by a myriad of drugs from almost every pharmacologic class. Octreotide is a somatostatin analog that has been used to treat variceal bleeding, acromegaly, and severe diarrhea associated with metastatic tumors, and to reduce symptoms in the setting of malignant bowel obstruction and pseudoobstruction. The most common adverse effects associated with octreotide include pain at the injection site and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A case report mentioned a patient who took tamsulosin (ATC code: G04CA02) at 0.4 mg/day with other drugs including octreotide and was diagnosed with neutropenia. 28 …”
Section: Resultsmentioning
confidence: 99%
“…A case report mentioned a patient who took tamsulosin (ATC code: G04CA02) at 0.4 mg/day with other drugs including octreotide and was diagnosed with neutropenia. 28 …”
Section: Resultsmentioning
confidence: 99%
“…Tse et al reported a case of 87-year-old man who developed neutropenia immediately after administration of three doses of subcutaneous octreotide. [19] Clinicians should be aware of this adverse reaction when treating pancreatitis with octreotide.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 Likewise, octreotide is effective but shows the risk of aggravating neutropenia. 20 Thus, focusing on the prevention of the occurrence of IID, rather than the treatment, would be valuable. In the current reports on prevention measures of IID, probiotic, 21 activated charcoal, 22 and neomycin 23 are often discussed.…”
Section: Introductionmentioning
confidence: 99%